Analisis Persepsi Dampak Relokasi Pedagang Terhadap Pendapatan Pedagang (Studi Pada Pasar Anyar Singaraja, Kecamatan Buleleng) - Putu Alvina Shanda; Made Ary Meitriana; I Nyoman Sujana (Universitas Pendidikan Ganesha, 2025)
This study examined the impact of trader relocation on their income at Pasar Anyar Singaraja. The local government relocated traders from roadside areas to the second floor of the market building to organise the market area more effectively. The study employed a qualitative descriptive approach using a case study method. Data were collected through interviews, direct observations, and documentation involving traders, customers, and market management. The results show that most traders experienced a significant decrease in income after moving to the upper floor. This decline was caused by fewer customers, a less strategic location, and inconvenient access. Many customers, especially elderly people and those with young children, were reluctant to go upstairs. The study concludes that relocation without careful planning and effective without careful planning and effective communication can harm small traders. Therefore, future relocations should involve traders, consider customer habits, and ensure adequate supporting facilities are provided.